Retour de flamme 05 : la fabuleuse enfance du cinéma - Bromberg, Serge; Lange, Eric; Simon, Anne; Georgiadès, Sylvie (Paris : Lobster Films, 2006)
- Arthéme swallows his clarinet / Eclipse / cast, Ernest Servaes (France, 1912, 3:54) ##- The cook / Paramount / producer, Roscoe "Fatty" Arbuckle ; cast, Fatty Arbuckle, Buster Keaton, Al St. John (USA, 1918, 21:00) ##- All this and rabbit stew / Warner / producer, Tex Avery (USA, 1941, 6:28) ##- Love and advertising / Sédif / producer, Léo Mittler ; cast, Claude Lehmann, Alma Mills (France, 1932, 25:30) ##- An excursion to the moon / Pathe / producer, Segundo de Chomón (France, 1908, 6:45) ##- La La samaritaine (docu., France, 1930, 9:30) ##- Publi-ciné Idylle (1945) Bonne Humeur (1945) Roller catch (1945) Qui sera Miss Philips (1950) ##- Ils demenagent (1950) ##- Cette nuit-la / cast, Jacques Tati (1935) (France 7:30) ##- By Indian post / Universal Film / producer, John Ford ; cast, Pete Morrison, Magda Lane (USA, 1919, 13:20) ##- Cyrano de Bergerac / producer, Clément-Maurice ; cast, Coquelin Ainé (France, 1900, 2:00) ##- Ain't she sweet / Fleischer Studios / producer, Dave Fleischer ; cast, Lillian Roth (USA, 1933, 7:13)
French or English language tracks with optional English or French subtitles.
film
Keywords: ACAD